1988
DOI: 10.1111/j.1365-2044.1988.tb05413.x
|View full text |Cite
|
Sign up to set email alerts
|

Low volume, high concentration block of the sciatic nerve

Abstract: SummarySciatic nerve block was performed in two groups of patients using a low power peripheral nerve stimulator to aid nerve location. The demonstration that greater accuracy of needle placement can be achieved by use of a low power peripheral nerve stimulator during sciatic blockade, should permit the use of smaller volumes and, therefore, higher concentrations of local anaesthetic solutions. Accurate needle placement and the use of concentrated solutions should result both in a reduction of latency and in g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 6 publications
(1 reference statement)
0
11
0
Order By: Relevance
“…Little is known about the relative importance of local anesthetic volume versus concentration for peripheral nerve blockade24,25,31,33) or for spinal pain blocks. The optimum dose of local anesthetics in spinal pain blocks is adjusted to prevent pain, minimize motor block, and prolong block duration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Little is known about the relative importance of local anesthetic volume versus concentration for peripheral nerve blockade24,25,31,33) or for spinal pain blocks. The optimum dose of local anesthetics in spinal pain blocks is adjusted to prevent pain, minimize motor block, and prolong block duration.…”
Section: Discussionmentioning
confidence: 99%
“…This report suggested that when a large volume of local anesthetics (ropivacaine) was administered, the placement accuracy was less critical and motor block was associated with the local anesthetic concentration. In studies of sciatic nerve blocks, the authors concluded that administering a low volume and a high concentration of local anesthetic was associated with a shorter time to onset of complete sensory and motor block33) and a longer duration of analgesia31) than a larger volume and a lower concentration of local anesthetic. Individual patients may have different responses to the same dose of the same drug delivered in the same location.…”
Section: Discussionmentioning
confidence: 99%
“…A number of recommendations have been made in an effort to reduce the risk of this complication [6,7].…”
Section: Wiggle Technique For Orbital Blockmentioning
confidence: 99%
“…The relationship of local anesthetic concentration and the volume needed to achieve analgesia without a motor block varies with the anatomical location where it is given [5][6][7][8][9][10]. For epidurally administered local anesthetics, concentration is the primary determinant of the depth of motor block whereas the total mass of local anesthetic determines spread [5].…”
mentioning
confidence: 99%
“…Smith and Siggins (1988) anesthetized. This is the usual situation in which regional anesthesia is performed in children (Bosenberg, 1995).…”
Section: Potential Problemsmentioning
confidence: 99%